2018
DOI: 10.18280/ijht.360443
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of heat transfer over a flat plate with a triangular vortex generator

Abstract: In the present work, the effect of the angle of a triangular vortex generator on the heat transfer of a flat plate is investigated. Incompressible three-dimensional fluid flows in a channel with constant temperature boundary condition. The results showed that the Nusselt number increases and the pressure decreases with the Reynolds number. It is demonstrated that the increase in the angle from 30° to 90° has a significant effect on the Nusselt number. The pressure drop remains constant at a 60° angle with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Vortex generator augments film cooling by the creation of secondary vortices [17]. Flow and heat transfer characteristics are enhanced by implementing vortex generators [18][19][20][21][22]. The results of reference 18 revealed that the longitudinal vortices have an important effect on the heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Vortex generator augments film cooling by the creation of secondary vortices [17]. Flow and heat transfer characteristics are enhanced by implementing vortex generators [18][19][20][21][22]. The results of reference 18 revealed that the longitudinal vortices have an important effect on the heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…As a recent work about the convection enhancement by the passive method, Bayareh et al [6] simulated the heat transfer over a flat plate with a triangular vortex generator. In that work, the set of governing equations was solved by the CFD technique to determine the velocity and temperature fields inside the lamin ar convection airflow under a vortex generator.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the maximum Nusselt number is achieved when the angle of attack is 29. Bayareh et al [17] studied the effect of angle of a triangular vortex generator for laminar flow on enhancing heat transfer in a channel. The authors indicated that the heat transfer performance is considerably affected by increasing the angle from 30° to 90°.…”
Section: Introductionmentioning
confidence: 99%